Determination of economic growth in Bali province 2004-2023 - Fadhilah, Nur Lailatul; Sukadi, Agung Slamet (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2026)
The purpose of this study is to examine how household consumption, literacy rates, poverty rates, and per capita income affect economic growth in Bali Province. This study uses a macro analysis unit covering 9 regencies/cities in Bali Province during the period 2004-2023, the data used is secondary panel data sourced from official reports of the Central Statistics Agency (BPS). The Panel Data Model was chosen to overcome the potential endogeneity between variables and capture the effect of welfare persistence from year to year across all regencies/cities in Bali. The results of the analysis show that the poverty variable does not have a significant impact on economic growth, meaning that changes in poverty levels do not have a direct impact on Bali's economic growth rate. Economic growth is negatively and significantly influenced by the per capita income variable, as shown in the uneven distribution of income across various regions, economic growth does not always follow the increase in per capita income. Increases consumption Public participation can stimulate regional economic activity, as evidenced by the significant positive impact of household consumption on economic growth. Furthermore, economic growth is positively and significantly influenced by the literacy rate, indicating that increasing literacy rates among the Balinese population is crucial for increasing labor productivity. This confirms that improving the quality of human resources and strengthening people's purchasing power are key factors in driving sustainable economic growth in Bali Province.